P1529 Impact of the new PH guidelines on echocardiographic definition leading to double demand of right heart catheterization. (17th January 2020) - Fauvel, C; Raitiere, O; Burdeau, J; Si Belkacem, N; Bauer, F
Abstract: Background: Doppler echocardiography is the most widespread and well-recognized technique for the screening of patients with pulmonary hypertension (PH). When tricuspid regurgitation peak velocity (TRPV) ≥3.4 m/s, right heart catheterization is requested to confirm mean pulmonary artery pressure >25 mm Hg. In the proceedings from the 6th world symposium on pulmonary arterial hypertension recently released, the new definition of PH has been lowered to mean pulmonary artery pressure > 20 mm Hg. Purpose: The purpose of our work was twofold : i) to determine a new cut-off value for TRPV to accommodate the new hemodynamic definition of PH, ii) to investigate the impact on the demand of right heart catheterization (RHC) from our echo CORE lab. Methods: We extracted and analyzed both the haemodynamic and echocardiographic records of 130 patients who underwent investigations the same day. Tricuspid regurgitation peak velocity was measured in apical-4 chamber view using continuous-wave doppler modality and compared to mean pulmonary artery pressure recorded from fluid-filled catheter. Results: Tricuspid regurgitation peak velocity has a weak correlation with mean pulmonary pressure (y = 9.2x-2.2, r² = 0.22, p < 0.01). Targeting a mean pulmonary pressure on right heart catheterization of 20 mm Hg for the definition of PH, receiver operating characteristic curve analysis demonstrated a good association between TRPV and PH diagnosis (area under the curve, 0.78 ; p < 0.001). The cut-off value obtained for TRPV was 3.0 m/s (Se = 0.78, Sp = 0.37). From 01/01/18 to 31/12/18, 2539 out of 6215 had TRPV recorded from which 283 had TRPV ≥ 3.0 m/s (24, 1%) and 615 had TRPV ≥ 3.4 m/s (11, 1%). When applied to a community population the new TRPV cutoff > 3m/s used as surrogate for mean pulmonary artery pressure > 20 mm Hg may produce a 111% increase of right heart catheterization demand. Conclusions: The new definition of pulmonary hypertension (invasive mean pulmonary artery pressure > 20mm Hg) necessitates revisiting tricuspid regurgitation peak velocity > 3 m/s as a screening test leading to more than twice RHC demand.